Developmental Changes in the Corpus Callosum from Infancy to Early Adulthood: A Structural Magnetic Resonance Imaging Study - Tanaka-Arakawa, Megumi M.; Matsui, Mie; Tanaka, Chiaki; Uematsu, Akiko; Uda, Satoshi; Miura, Kayoko; Sakai, Tomoko; Noguchi, Kyo (PloS one, 2015)
Previous research has reported on the development trajectory of the corpus callosum morphology. However, there have been only a few studies that have included data on infants. The goal of the present study was to examine the morphology of the corpus callosum in healthy participants of both sexes, from infancy to early adulthood. We sought to characterize normal development of the corpus callosum and possible sex differences in development. We performed a morphometric magnetic resonance imaging (MRI) study of 114 healthy individuals, aged 1 month to 25 years old, measuring the size of the corpus callosum. The corpus callosum was segmented into seven subareas of the rostrum, genu, rostral body, anterior midbody, posterior midbody, isthmus and splenium. Locally weighted regression analysis (LOESS) indicated significant non-linear age-related changes regardless of sex, particularly during the first few years of life. After this increase, curve slopes gradually became flat during adolescence and adulthood in both sexes. Age of local maximum for each subarea of the corpus callosum differed across the sexes. Ratios of total corpus callosum and genu, posterior midbody, as well as splenium to the whole brain were significantly higher in females compared with males. The present results demonstrate that the developmental trajectory of the corpus callosum during early life in healthy individuals is non-linear and dynamic. This pattern resembles that found for the cerebral cortex, further suggesting that this period plays a very important role in neural and functional development. In addition, developmental trajectories and changes in growth do show some sex differences.